Engineering geomorphological and InSAR investigation of an urban landslide, Gisborne, New Zealand - Matthew E. Cook; Martin S. Brook; Ian J. Hamling; Murry Cave; Jon F. Tunnicliffe; Rachel Holley; David J. Alama (Landslides, 2022)
The East Coast region of New Zealand has some of the highest erosion rates in the world, due to its proximity to an active plate boundary, susceptibility to high-intensity storms and steep terrain underlain by young soft sedimentary rock and soil. In the city of Gisborne, expansion of residential blocks into steeper terrain in peri-urban areas has required improved capacity for the characterisation and monitoring of slope stability. Landslides have affected several properties and have destroyed infrastructure. Slope failure commonly occurs during heavy rainfall events when slow-moving retrogressive slides transition into earthflows and mudflows. In this study, we used in situ sampling and testing methods combined with remote sensing techniques to provide an understanding of the pre-failure and post-failure behaviour of an urban landslide in Gisborne. High-resolution aerial imagery, unmanned aerial vehicle imagery and light detection and ranging data revealed slope morphology and contours of prehistoric failures in the area, and highlighted the more recent impacts of deforestation on slope stability. Furthermore, Sentinel-1 InSAR analysis determined that gradual deformation began in 2017, following two ex-tropical cyclone events. Deformation downslope continued until an initial failure in July 2020. Following that event, some parts of the slope proceeded to accelerate, leading to a further reactivation event in November 2021, following heavy rainfall. During this November 2021 event, average line of sight velocities ranged from −7.9 to −11.2 mm/year, and deformation rates in the vertical direction (related to rotational slumping) averaged −11.2 to −11.9 mm/year, consistent with field observations.